The synthetics fibers effect in the concrete plastic properties - Portella Montardo, Julio (Revista Ingeniería de Construcción, 2005)
This paper provides a bibliographic review regarding some physical and mechanical properties of polypropylene fibers and their use in concrete. The inclusion of fibrous reinforcements in concrete is growing up. However this association is only experimental and some theoretical concepts which could help us to understand the interaction mechanism fiber-matrix are passed over. Therefore the new materials development potential and its experimental results comprehension are restricted. This paper has two purposes: 1) to present the concepts regarding composite materials and 2) to present the polypropylene fibers effect in the concrete plastic properties. The conclusion is that the low elasticity modulus and the high elongation of polypropylene fibers reduce the bleeding and plastic shrinkage cracking in concrete, enhancing the surface properties and the durability of hardened concrete products. This review intends to connect some experimental results to theoretical concepts about composite materials.